Single-cell branching morphogenesis in the Drosophila trachea - Best, Benedikt (Developmental biology, 2019)
The terminal cells of the tracheal epithelium in Drosophila melanogaster are one of the few known cell types that undergo subcellular morphogenesis to achieve a stable, branched shape. During the animal's larval stages, the cells repeatedly sprout new cytoplasmic processes. These grow very long, wrapping around target tissues to which the terminal cells adhere, and are hollowed by a gas-filled subcellular tube for oxygen delivery. Our understanding of this ramification process remains rudimentary. This review aims to provide a comprehensive summary of studies on terminal cells to date, and attempts to extrapolate how terminal branches might be formed based on the known genetic and molecular components. Next to this cell-intrinsic branching mechanism, we examine the extrinsic regulation of terminal branching by the target tissue and the animal's environment. Finally, we assess the degree of similarity between the patterns established by the branching programs of terminal cells and other branched cells and tissues from a mathematical and conceptual point of view.
Gesehen am 11.12.2019
Published online: 04 December 2018